2021
DOI: 10.1371/journal.pone.0245500
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in a cohort of HIV-infected patients initiating antiretroviral therapy in an outpatient setting in Ethiopia

Abstract: Aim To evaluate the prevalence and associated factors of abnormal renal function among Ethiopian HIV-infected patients at baseline prior to initiation of antiretroviral therapy (ART) and during follow-up. Methods We conducted a retrospective observational cohort study of HIV infected patients who initiated ART at the outpatient ART clinic of Mehal Meda Hospital of North Shewa, Ethiopia from January 2012 to August 2018. Demographic and clinical data were abstracted from the medical records of patients. Renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(95 reference statements)
0
5
0
2
Order By: Relevance
“…reported a decline in renal function in patients being started on HAART in Ethiopia. 23 Szczech et al also reported an absence of any beneficial effect of HAART or viral suppression on the decline in renal function observed in their study. 24 Pujari et al, through a study conducted at both the Institute of Infectious Diseases (IID) Pune, Western India, and the Royal Free Hospital (RFH) London, observed that there was a statistically significant decline in eGFR from baseline at 6 and 24 months at both the sites.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…reported a decline in renal function in patients being started on HAART in Ethiopia. 23 Szczech et al also reported an absence of any beneficial effect of HAART or viral suppression on the decline in renal function observed in their study. 24 Pujari et al, through a study conducted at both the Institute of Infectious Diseases (IID) Pune, Western India, and the Royal Free Hospital (RFH) London, observed that there was a statistically significant decline in eGFR from baseline at 6 and 24 months at both the sites.…”
Section: Discussionmentioning
confidence: 70%
“…6 A 6-year cohort by Fiseha et al reported a decline in renal function in patients being started on HAART in Ethiopia. 23 Szczech et al also reported an absence of any beneficial effect of HAART or viral suppression on the decline in renal function observed in their study. 24…”
Section: Discussionmentioning
confidence: 70%
“…Among people living with HIV, the kidney is affected by direct HIV infection of the renal epithelial cells, deposition of immune complexes, and toxicities from drugs used to treat HIV (Tenofovir Disoproxil Fumarate (TDF), protease inhibitors, or HIV-related opportunistic infections (amphotericin B) (20)(21)(22). Although ART initiation is protective against kidney diseases, especially HIV-associated nephropathy (23), there is evidence of increased prevalence of kidney diseases after ART initiation (24)(25)(26). CKD is among the 10 most common non-infectious complications of HIV in the US (20,27).…”
Section: Introductionmentioning
confidence: 99%
“…В связи с чем, важно мониторировать не только уровень иммунорегулирующих клеток, но и функцию почек у лиц с ВИЧ-инфекцией вне зависимости от стадии заболевания. T. Fiseha и A. Gebreweld оценивали распространенность и факторы, влияющие на величину СКФ среди эфиопских ВИЧ-позитивных пациентов на исходном уровне до начала АРТ и во время последующего наблюдения [53]. Исследователи оценивали функцию почек с помощью СКФ, рассчитанной по методике MDRD.…”
unclassified
“…Отдельно следует отметить, что в указанном исследовании распространенность почечной недостаточности увеличилась с 19,8% (исходно) до 22,1% в течение периода наблюдения. В течение всего периода наблюдения факторами, способствующими развитию почечной недостаточности, оказались пожилой возраст (ОШ 3,85, 95% ДИ 2,03-7,31), женский пол (ОШ 4,18, 95% ДИ 2,08-8,40), низкий исходный уровень CD4-клеток (ОШ 2,41, 95% ДИ 1,24-4,69), низкое текущее количество CD4 (ОШ 2,32, 95% ДИ 1,15-4,68), высокий ИМТ (ОШ 2,91, 95% ДИ 1,49-5,71) и низкий гемоглобин (ОШ 3,38, 95% ДИ 2,00-7,46) [53].…”
unclassified